Agglomeration in a vertically-linked oligopoly - Pontes, José Pedro (2010)
This paper examines the location of three vertically-linked firms. In a spatial economy composed of two regions, a monopolist firm supplies an input to two consumer goods firms that compete in quantities. The interaction between the firms is modelled by means of a three-stage game, where the firms first select locations, then the upstream firm chooses thedelivered prices of the intermediate good, and finally the downstream firmsselect quantitiesofthe final good. It is concluded that agglomeration is more likely to occur when the ratio between the transport cost of the intermediate good and the transport cost of the final good is higher. If this proportion is low, the existence of an agglomeration varies nonmonotonically with transport costs.